2014
DOI: 10.1038/pcan.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside disialosyl globopentaosylceramide is an independent predictor of PSA recurrence-free survival following radical prostatectomy

Abstract: 5F3 expression reflects the clinical and pathological features of prostate cancer and is correlated with the outcomes following RP. Further studies are necessary to clarify the functional roles of DSGb5 and establish a novel biomarker for prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…Previous studies showed associations between glycolipids and malignant potential of melanomas, breast cancers, and prostate cancers . In accordance, glycolipids were expressed on various cell surfaces, and their glycan structures were modified by several glycosyltransferases.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies showed associations between glycolipids and malignant potential of melanomas, breast cancers, and prostate cancers . In accordance, glycolipids were expressed on various cell surfaces, and their glycan structures were modified by several glycosyltransferases.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies showed associations between glycolipids and malignant potential of melanomas, (34) breast cancers, (35,36) and prostate cancers. (37) In accordance, glycolipids were expressed on various cell surfaces, and their glycan structures were modified by several glycosyltransferases. Moreover, these glycolipids regulated not only cell-cell interactions by glycan-glycan interactions (38) but also regulated cell adhesion and migration by glycolipid-tetraspanin or glycolipid-caveola interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Gangliosides are considered attractive targets for the generation of new antitumor molecules (Doronin et al, 2014;Shimada et al, 2014). mAb-based anticancer therapies are increasingly being tested to obtain an effective immune response against cancer cells (Reichert, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In our recent report, immunohistochemical analysis of 130 radical prostatectomy specimens revealed that DSGb5 expression was significantly correlated with lymphovascular invasion of prostate cancer cells (Shimada et al 2014). In the process of cancer metastasis, lymphovascular invasion is the critical step occurring subsequent to cellular migration.…”
Section: Discussionmentioning
confidence: 99%